The Expertise of Traditional Healers in Using Coconut Oil as a Traditional Treatment for Bone Fracture Recovery in Aliantan Village - Ramadhani, Putri (Indonesian Journal of Medical Anthropology, 2024)
This research aims to explore more deeply the skills of traditional healers in using coconut oil as a traditional treatment for fracture recovery in Aliantan Village. The research method used is a qualitative approach with a case study method, which involves interviews with traditional healers and patients who have undergone treatment, as well as observations to strengthen the data. The research results show that traditional medicine with coconut oil is still relevant and appreciated by the people of Aliantan Village, even though there is a shift towards modern medicine. Broken healers use coconut oil with massage and bone repositioning techniques to speed up the healing process. The conclusion of this research is that the skills of traditional healers and the use of coconut oil remain an important part of cultural heritage and local knowledge that continues to be preserved. Keyword: Shaman, Bones, Oil, Coconut, Treatment